IMPLEMENTATION OF GERMAS, ESPECIALLY THE ASPECT OF HEALTHY ENVIRONMENT IN PULAU ATAS SAMARINDA - Apriyani, Apriyani; Suwignyo, Suwignyo; Kusumawati, Rindha Mareta; Wulandari, Kartina (HEARTY, 2024)
The Healthy Living Community Movement (Germas) is a planned activity carried out jointly with awareness, willingness, and ability to behave healthily to improve the quality of life. People generally see health as related to lifestyle, if they are sick then it must have something to do with food even though the influence of the environment on health is quite large. So the purpose of this study is to find out and educate the public on environmental health. This study uses descriptive quantitative research design with the population of Pulau Atas in Samarinda, selecting 100 respondents with incidental sampling technique and using interviews to find out the condition of the community. Respondents who have trash bins are 76, who do waste sorting are only 38, recycling waste is 9, who recycle waste by making compost is 1 person and recycle waste by making handicrafts are 8. Respondents who have latrines are 99. The majority of respondents used PDAM water as many as 86 people and respondents who consumed refillable gallon water were 69. Almost most of the community has understood implementing a healthy environment such as garbage, use of latrines and clean water for daily activities. Only a small part of the community does not apply a healthy environment. However, waste management is still not maximally carried out.